Service Quality And Profit Sharing Perception On Loyalty With Satisfaction Mediation (Study Bank Syariah Indonesia Kcp Malang Sutoyo) - Janan, Akhmad Syifa’ul; Firmansyah, Fani (WADIAH, 2025)
The purpose of this study is to determine the influence of service quality and profit sharing perception on loyalty by satisfaction mediation in Indonesian Islamic bank KCP Malang SutoyoThis study uses a quantitative method with a quantitative descriptive approach. Research sources use observation, interviews, documentation and cursors. The statistical data processing is SEM tools for Outer Model and Inner Model Measurement Analysis. The results of the study show that: 1) Service quality has a positive and significant effect on Customer Loyalty of Bank Syariah Indonesia KCP Malang Sutoyo due to good service quality factors such as: Reliability, Responsiveness, Assurance, Empathy, Tangibles. This factor greatly affects customers in assessing the quality of services for goods and services provided by the Bank, 2) Profit Sharing Reception Does Not Affect Bank Customer Loyalty Because the majority of customers do not know much about the profit sharing system in Indonesian Islamic banks, especially at KCP Malang Sutoyo, 3) Service Quality Has a Positive and Significant Effect on Customer Loyalty (Y) Through Satisfaction (Z) Case Study on Bank Customers with indicators of meeting expectations and always buying products, 4) Profit Sharing Perception has no effect on Customer Loyalty. This happened because the majority of Bank Syariah Indonesia KCP Malang Sutoyo customers used their savings in the wadiah contract, which of course there was no profit-sharing system in the contract  Kata Kunci: Influence, quality of Service, Perception of profit sharing, Satisfaction, and loyalty.